Analisis Sumber Hukum Islam: Telaah Metode dan Perdebatan - Hidayat, Rian; F, Fatmawati; Sultan, Lomba (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research stems from the complexity of interpreting Islamic legal sources and the disagreement among scholars regarding the methodology of its analysis. The primary objective of the study is to provide a deeper understanding of the methods used in analyzing Islamic legal sources and to elucidate the debates that arise in this context. The research methodology employed is a literature review, involving the collection and analysis of key literature discussing various methods of analyzing Islamic legal sources and the associated debates. The approach utilized in this research is a normative approach, allowing the researcher to evaluate the methods of analyzing Islamic legal sources from the perspective of existing legal norms. This study holds significance in enriching academic insights into the approach of analyzing Islamic legal sources. The research outcomes are expected to contribute to a better understanding of the complexity and conceptual framework underlying the process of analyzing Islamic legal sources. Practical implications of this research include guidance for researchers, legal practitioners, and students to better comprehend how to navigate differences in approaches when analyzing Islamic legal sources.